Minimum Detour Index of Tricyclic Graphs - Wei Fang; Zheng-Qun Cai; Xiao-Xin Li (Journal of Chemistry)
The detour index of a connected graph is defined as the sum of the detour distances (lengths of longest paths) between unordered pairs of vertices of the graph. The detour index is used in various quantitative structure-property relationship and quantitative structure-activity relationship studies. In this paper, we characterize the minimum detour index among all tricyclic graphs, which attain the bounds.